Effects of Calorie Restriction in Obese Older Adults: The CROSSROADS Randomized Controlled Trial. (21st December 2016) - Ard, Jamy D; Gower, Barbara; Hunter, Gary; Ritchie, Christine S; Roth, David L; Goss, Amy; Wingo, Brooks C; Bodner, Eric V; Brown, Cynthia J; Bryan, David; Buys, David R; Haas, Marilyn C; et al.
Abstract: Background: We lack a comprehensive assessment of the risks and benefits of calorie restriction in older adults at high risk for cardiometabolic disease. Calorie restriction may reduce visceral adipose tissue (VAT) but also have negative effects on lean mass and quality of life. Methods: We conducted a 52-week, randomized controlled trial involving 164 older adults with obesity taking at least one medication for hyperlipidemia, hypertension, or diabetes. Interventions included an exercise intervention alone (Exercise), or with diet modification and body weight maintenance (Maintenance), or with diet modification and energy restriction (Weight Loss). The primary outcome was change in VAT at 12 months. Secondary outcomes included cardiometabolic risk factors, functional status, and quality of life. Results: A total of 148 participants had measured weight at 12 months. Despite loss of −1.6% ± 0.3% body fat and 4.1% ± 0.7% initial body weight, Weight Loss did not have statistically greater loss of VAT (−192.6 ± 185.2 cm 3 ) or lean mass (−0.4 ± 0.3 kg) compared with Exercise (VAT = −21.9 ± 173.7 cm 3 ; lean mass = 0.3 ± 0.3 kg). Quality of life improved in all groups with no differences between groups. No significant changes in physical function were observed. Weight Loss had significantly greater improvements in blood glucose (−8.3 ± 3.6 mg/dL, p < .05) and HDL-cholesterol (5.3 ± 1.9, p < .01) compared with Exercise. There were no group differences in the frequency of adverse events. Conclusions: While moderate calorie restriction did not significantly decrease VAT in older adults at high risk for cardiometabolic disease, it did reduce total body fat and cardiometabolic risk factors without significantly more adverse events and lean mass loss.